A comparison of pilot-scale supersonic direct steam injection to conventional steam infusion and tubular heating systems for the heat treatment of protein-enriched skim milk-based beverages. (March 2019) - Kelleher, Clodagh M.; Tobin, John T.; O'Mahony, James A.; Kelly, Alan L.; O'Callaghan, Donal J.; McCarthy, Noel A.
Abstract: Direct supersonic steam injection, direct steam infusion, and indirect tubular heating were each applied to protein-enriched skim milk-based beverages with 4, 6 and 8% (w/w) total protein, and the effect of final heat temperature on the physical properties of these beverages was investigated. Supersonic steam injection resulted in significantly lower levels of denaturation of β-lactoglobulin (34.5%), compared to both infusion (76.3%) and tubular (97.1%) heating technologies. Viscosity, particle size and accelerated physical stability of formulations did not differ significantly between the heating technologies, while noticeable colour differences due to heat treatment (mainly attributed to increasing b* value) were observed, particularly for tubular heating. Overall, the extent of protein denaturation in high-protein dairy products was significantly influenced by the particular heating technology applied. The application of supersonic steam injection technology, with rapid heating and high shear characteristics, may enable differenciated product characteristics for ready-to-drink ambient-delivery high-protein dairy beverages. Industrial relevance: The design and application of novel direct supersonic steam injection technology was comprehensively studied and found to provide significant benefits over direct steam infusion and indirect tubular heating technologies for skim milk-based protein beverages. This type of injection heating system resulted in heat-treated formulations with lower levels of denatured whey proteins, compared to tubular and infusion heating, offering an alternative opportunity to the industry in terms of producing shelf-stable dairy protein beverages. Highlights: Supersonic steam injection provides rapid heating and high shear. Substantial native whey protein retention compared to tubular and infusion heating No difference in accelerated physical stability for heating technologies May enable new product development opportunities